Search for the Decay of the Higgs Boson to Charm Quarks with the ATLAS Experiment - Aaboud, M. (2018)
A direct search for the Standard Model Higgs boson decaying to a pair of charm quarks is presented. Associated production of the Higgs and Z bosons, in the decay mode ZH → ` + ` − cc¯ is studied. A dataset with an integrated luminosity of 36.1 fb−1 of pp collisions at √ s = 13 TeV recorded by the ATLAS experiment at the LHC is used. The H → cc¯ signature is identified using charm-tagging algorithms. The observed (expected) upper limit on σ(pp → ZH) × B(H → cc¯) is 2.7 (3.9 +2.1 −1.1 ) pb at the 95% confidence level for a Higgs boson mass of 125 GeV, while the Standard Model value is 26 fb.